KOMUNIKASI PERSUASIF KOMUNITAS YUK BERBAGI PEKANBARU DAŁAM MENARIK PARTISIPASI DONATUR UNTUK MELAKUKAN KEGIATAN SOSIAL DI KOTA PEKANBARU - Lee, Ridho Evans; Awza, Rusmadi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Social community is a group that is in each of its members are united by a common vision and mission as well as social-themed destination. One form of social communities in Pekanbaru is Yuk Berbagi Pekanbaru Community. Come Share Pekanbaru community engaged in social duty to help people who need help around Pekanbaru. To create an activity, requires funding and donors for the smooth running of the activities undertaken. Therefore, to attract the participation of donors, Yuk Berbagi Pekanbaru Community conduct persuasive communication. The purpose of this study is to investigate the persuasive communication techniques, persuasive communication messages,This study used qualitative research methods. Research conducted at the Secretariat Yuk Berbagi Pekanbaru on Jl. Pemuda No. 22/10 Tenayan Raya, Pekanbaru. Selection of informants done by using purposive. As for the informants of this study is the chairman of the community of Yuk Berbagi Pekanbaru, two community members of Yuk Berbagi Pekanbaru, two regular donors Yuk Berbagi Pekanbaru community and one person did not keep a community donors Yuk Berbagi Pekanbaru. Data collection techniques used for conducting research is by observation, interview and documentation. While the validity of the data that researchers use is extended participation, triangulation as well as the adequacy of reference.The results showed that, in the persuasive communication, the Community Yuk Berbagi Pekanbaru using four techniques that technique putting it up to you, bandwagon technique, the technique say it with flower and raessuarnce techniques. Meanwhile, persuasive messages used Community Yuk Berbagi Pekanbaru is the use of verbal messages and nonverbal messages. During persuasive communication, communicant which in this case is the donor always give a positive response and impression. In addition, when making a persuasive communication, the Community Yuk Berbagi Pekanbaru also use the media as a container or channel message. The media used Yuk Berbagi Community Pekanbaru is social media instagram.